Non-capitonnage method for surgical treatment of lung hydatid cysts - Eren, M. Nesimi; Balci, Akin E.; Eren, Şevval (Asia Publishing Exchange Pte Ltd, 2005)
Capitonnage is usually advocated for obliteration of the residual cavity after removal of a hydatid cyst. To assess a non-capitonnage method, results in 33 patients were compared with those of 80 patients who had capitonnage. The non-capitonnage patients had a shorter mean hospital stay and earlier radiologic improvement but higher morbidity than the capitonnage patients. Extended air leak caused significant morbidity in each group. Bronchoscopic intervention was needed for atelectasis in 1 patient. There was no mortality in either group. In the follow-up period, no late complication or recurrence was observed in non-capitonnage patients. Among the capitonnage patients, 2 had bronchiectasis, and suture material expectoration occurred in one. The non-capitonnage method may be a good alternative to the capitonnage procedure for lung hydatid cyst. Better management of bronchial openings should improve the results of the non-capitonnage method.
Keywords: suture material; adult; article; atelectasis; bronchiectasis; bronchoscopy; controlled study; female; follow up; hospitalization; human; lung hydatid cyst; lung surgery; major clinical study; male; morbidity; mortality; statistical significance; surgical technique; thorax radiography; treatment outcome; wound dehiscence